Modeling the spatial relationship between urban ecological resources and the economy. (1st February 2018) - Liu, Hongxiao; Han, Baolong; Wang, Lan
Abstract: The relationship between a city's economic development and the ecological resource cost of that development is an important area of research, although the results vary between different study areas and with methods of inquiry. Using spatial match degree and econometric methods, urban economic success, as indicated by GDP and ecological resource base as indicated by vegetation cover (NVDI), for cities along the Beijing to Guandong high-speed railway were compared. Then those samples were divided into four different terrain area groups for a deeper analysis. Finally, a negative correlation between ecological resource and economy was revealed. A few different detailed spatial characteristics of the environmental costs of economic development were found in the different terrain areas. And, most cities consuming more environmental resources than they were expected according to their economic scale, which was thought unsustainable. Highlights: Sample cities located along the Chinese key railway cover 4 different terrains. The spatial match degree analysis is an original method for spatial extreme points. Negative correlation between ecological resource and economy was found. But this relationship has different characters in 4 terrain areas respectively. Most cities in the study area are still in an unsustainable development pattern.